Sustainability and Traditional Criteria in Supplier Selection and Order Allocation Decisions : A Finnish Industry Perspective - Nanayakkara, Hirushi (My University, 2026)
The present study investigates how buyers in the Finnish industrial technology and automation industry perceive the importance of sustainability criteria relative to traditional supplier selection criteria, and how these perceptions influence business allocation decisions. The research addresses a gap in the sustainable procurement literature by focusing on buyer perceptions in a real industrial context, rather than relying solely on conceptual models or hypothetical decision scenarios. The study is guided by Institutional Theory and the Resource-Based View, which together help explain how external sustainability pressures and internal strategic capabilities shape procurement behaviour. A quantitative research design was used, and primary data were collected through a survey of 95 respondents involved in purchasing-related decision-making in Finnish industrial technology and automation firms. The questionnaire measured the perceived importance of traditional criteria, including price, quality, delivery reliability, and technical capability, as well as sustainability-related criteria such as environmental practices, social practices, governance, and compliance. The data were analysed using descriptive statistics and inferential analysis to identify differences in criterion importance and to assess whether sustainability predicts supplier selection and allocation decisions beyond traditional factors. The results of the study show that buyers prioritize traditional purchasing criteria more strongly than sustainability criteria, although sustainability remains relevant in decision-making. Price, product/service quality, and delivery reliability received the highest importance ratings, while governance and compliance were the most highly valued sustainability-related criteria. The findings suggest that sustainability plays a stronger role in how business is distributed among suppliers than in the initial supplier selection stage within the Finnish industrial technology and automation industry. Overall, the study demonstrates that sustainable procurement in the Finnish industrial technology and automation industry is not about replacing traditional supplier selection criteria, but rather about balancing operational performance with sustainability expectations strategically and practically.
Keywords: enterprises; sustainable development; industry; supply chains; decision making; acquisition; industrial automation; logistics; suppliers; pliers; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business